Síndrome-fortuna: uma abordagem viável para a geração de números pseudoaleatórios no linux: uma abordagem viável para a geração de números pseudoaleatórios no linux - Daniel Rezende Silveira (2010)
Random numbers are used in various areas of computing, such as genetic programming, simulations and cryptography. In the latter, the random number generator takes a vital role, producing the initial secrecy for cryptographic protocols. This secret must be unknown to any adversary and will be used to ensure that the information remains secure. This work presents a random number generator based on the intractability of an NP-Complete problem, from the area of error-correcting codes, that use a nonheuristic approach for entropy collection. The generator, implemented in the Linux kernel, shows a good trade-o between e ciency and security and can be used as an alternative system interface for secure random number generation.